MENINGKATKAN HASIL BELAJAR MELALUI MEDIA CANVA DALAM PEMBELAJARAN IPA MATERI PENYESUAIAN DIRI MAKHLUK HIDUP TERHADAP LINGKUNGANNYA PADA SISWA KELAS V SD NEGERI 08 KOTA TERNATE - Marasabessy, Apridayani (Program Studi Pendidikan Ekonomi Institut Sain dan Kependidikan (ISDIK) Kie Raha Maluku Utara, 2025)
In this study, Canva media was used to improve student learning outcomes, especially in SD Negeri 8 Ternate City. This study used the PTK method with the aim of the study to determine/understand the use of Canva media in improving the ability of science learning outcomes of students at SD Negeri 8 Ternate City. The results obtained from this study The use of Canva media can improve student learning activities, seen from the average student learning activity in Cycle I of 63.25% and in cycle II of 77%, experiencing an average increase of 13.75%, with a Good predicate. Therefore, the use of Canva media can improve the learning outcomes of science subjects in grade V of SD Negeri 8 Ternate City, this is evidenced by the percentage of test results in cycle I and cycle II obtained based on written tests on students in the form of essay questions totaling 10 questions. In cycle I with a completeness result of 43.75% then experienced an increase in completeness of 81.25% in cycle II.